Enhancing in vitro osteogenic differentiation of mesenchymal stem cells via sustained dexamethasone delivery in 3D-Printed hybrid scaffolds based on polycaprolactone-nanohydroxyapatite/alginate-gelatin for bone regeneration - Parastoo Noory; Ahmad Reza Farmani; Jafar Ai; Naghmeh Bahrami; Mohammad Bayat; Somayeh Ebrahimi-Barough; Ali Farzin; Shima Shojaie; Hamed Hajmoradi; Abdolreza Mohamadnia; Arash Goodarzi (Journal of Biological Engineering)
Highlights Layer-by-layer 3D-printing was effectively applied to prepare a biomimetic combined structure composing hard composite (PCL-nHA) and soft hydrogel (Alg-Gel). 3D-printing scaffolds were used to control the delivery of dexamethasone (DEX) to enhance bone repair. DEX-loaded scaffolds promoted osteogenic differentiation and mineralization of human endometrial mesenchymal stem cells (hEnMSCs).